The role of Islamic education teachers’ personality in fostering academic resilience: A qualitative study - Ramadhani, Rofi'ah Khafidah; Hidayati, Sri; Surawan, Surawan (STAI Auliaurrasyidin Tembilahan, 2025)
Academic resilience refers to an individual’s ability to endure, recover, and adapt to academic challenges. This qualitative study explores the role of Islamic Religious Education (PAI) teachers’ personality competence in fostering students’ academic resilience at SMP Negeri 3 Katingan Hilir. Data were gathered through classroom observations (conducted twice in each of Grades VII, VIII, and IX), in-depth interviews with the school’s PAI teacher (the primary participant), and triangulation with three students and another teacher. Thematic analysis demonstrated that the teacher’s personality traits significantly enhanced students’ confidence, commitment, control, and composure. Specifically, 78% of observed student interactions showed improved self-regulation after teacher-led mentoring sessions. These findings align with Islamic values such as sabr (patience) and tawakkul (trust in God), which students adopted as psychological anchors during academic difficulties. The study identifies two key mechanisms underlying this influence: first, the teacher’s role-modeling of resilient behaviors, and second, faith-based coping strategies that frame challenges as opportunities for spiritual growth. These results suggest the importance of incorporating personality-focused teacher training and Islamic resilience frameworks into pedagogical practices, particularly in Muslim-majority educational settings.